Hellboy (1994), omnibus volume 2 ebook Strange places. - Mignola, Mike (Hellboy (1994), 2018)
Hellboy's complete story is presented for the first time in chronological order for the ultimate reading experience. This 416-page volume covers Hellboy's adventures from 1998 to 2005, reprinting Conqueror Worm, Strange Places, Into the Silent Sea, and ""The Right Hand of Doom, ""Box Full of Evil,"" and ""Being Human"" from The Right Hand of Doom and B.P.R.D. Being Human. Hellboy loses faith in the Bureau for Paranormal Research and Defense when they strap a bomb to one of his fellow not-quite-human agents. He gets answers about his destiny, like it or not, in over 300 pages of comics mostly drawn by Mignola, featuring award-winning guests Gary Gianni and Richard Corben. The four volume Hellboy Omnibus series along with the two volumes of The Complete Short Stories collect all of Mignola's award-winning Hellboy stories in chronological order for a definitive reading experience.